Survey of carotenes and vitamin A concentrations in cattle to be slaughtered in Thessaloniki - CHRISTODOULOPOULOS (Γ. ΧΡΙΣΤΟΔΟΥΛΟΠΟΥΛΟΣ) G.; ROUBIES (Ν. ΡΟΥΜΠΙΕΣ) N.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ) H.; PANOUSIS (Ν. ΠΑΝΟΥΣΗΣ) N.; PAPASTERIADIS (ΑΧ. ΠΑΠΑΣΤΕΡΙΑΔΗΣ) A. (Journal of the Hellenic Veterinary Medical Society, 2018)
The purpose of this survey was the study of vitamin A concentrations in cattle to be slaughtered in the area of Thessaloniki. For this purpose, research samples of blood and liver were collected from 165 cattle brought to different slaughter-houses of Thessaloniki, during the winter of the year 1998. Out of the 165 cattle to be slaughtered 76% presented lower than normal vitamin A in liver tissue (< 60 Mg/g W.M.), 14% had marginal (60-200 pg/g W.M.) and 10% normal concentration values (200-800 μg/g W.M.). It must be noted that, of the total 205 examined cattle 37% presented extremely deficient concentration of vitamin A in liver (< 14 μg/g W.M.), in these concentrations clinical signs of avitaminosis A are expected to appear. The statistic analysis of the research results show off that the liver and plasma concentrations of vitamin A were statistically significant lower in the fattening cattle (male and female) than in the adult reproductive cows. Statistically significant differences on liver and plasma vitamin A concentrations between male and female fattening cattle were not found. Statistically analysing this research it is confirmed for another time, that there is not closed linear relation between the vitamin A plasma concentrations and vitamin A liver concentrations. The linear regression equation that has been found between the vitamin A liver concentration (X) and the vitamin A plasma concentration (Y) is: Y=0,183+0,001 (±0,000***) X (***P<0,001, r2=0,130, 1,80 μg/g D.M.£X£350,08 μg/g D.M., 0,01 μg/ml£Y£3,28 μg/ml, n = 165). Closed linear regression was not found as well, between the vitamin A plasma concentrations and carotene plasma concentrations. The linear regression equation that has been found here between the vitamin A plasma concentration (X) and the carotene plasma concentrations (Y) is: Y=2,138+3,806 (±1,445*) X (*P<0,05, r2=0,057,0,01 μg/ml£Χ£3,28 μg/ml,0,00 μg/ml£Υ£23,36 μg/ml, n=165). The clinical signs that are described here for the animals with deficient levels of vitamin A (60 μg/g W.M. of liver) are limed to the following: poor performance, rough coat and ocular signs in the fattening cattle and infertility in the reproductive cows. Finally, in this research there is some evidence that the high carotene levels in reproductive cows (>4,8 μg/ml of plasma) for a long term may cause ovary dysfunction.